The Effect of Collaborative Reasoning On Indonesian University Students’ Literacy and Argumentation Skills - Firman Parlindungan; Mursyidin; Kurniasih; Refanja Rahmatillah; Rahmad Nuthihar; Said Oussou (JEELS (Journal of English Education and Linguistics Studies), 2023)
Since the global COVID-19 pandemic, traditional classrooms have no longer become accessible for everyone. Most teaching and learning process is conducted virtually. The use of interactive and dynamic pedagogy is needed to maintain the quality of learning, especially that enhance argumentation and literacy skills. This research aims to examine whether there are differences in literacy and argumentation skills of Indonesian university students before and after the implementation of Collaborative Reasoning (CR) approach during online learning. A quasi-experimental one-group pretest-and posttest design was employed. A total of 30 students taking Communication and Gender course were involved in this research. We developed a Reading Comprehension Test (RCT) to collect the literacy scores of the students and Cognitively Based Assessment of, for, and as Learning (CBAL) Argumentation Progression to measure argumentation scores. Using a paired samples t-test, the literacy and argumentation scores of the students before participating in CR were compared to their scores after participating in CR. The literacy and argumentation scores were significantly higher after participating in CR. This finding indicates that there is an increase in literacy and argumentation scores over time that was not likely to be due to chance. It is pivotal then for language educators to consider CR in their classrooms.